Matematyka

Autorzy:Adam Makowski, Tomasz Masłowski, Anna Toruńska

Wydawnictwo:WSiP

Rok wydania:2016

Niech x,y będą liczbami dodatnimi, a n-liczbą 4.29 gwiazdek na podstawie 7 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a) \ \ sqrt(x^n)*sqrt(x^(n+2)y^(2n))=sqrt(x^n*x^(n+2)*y^(2n))=sqrt(x^(n+n+2)y^(2n))=` `sqrt(x^(2n+2)y^(2n))=` `sqrt(x^(2n+2))*sqrt(y^(2n))=` 

`=sqrt(x^(2*(n+1)))*sqrt((y^n)^2)=sqrt((x^(n+1))^2)*y^n=x^(n+1)*y^n` 

`b) \ \ sqrt(x^(3n)y^(n+5))*sqrt(x^(5n)y^(3n+1))=sqrt(x^(3n)y^(n+5)x^(5n)y^(3n+1))=sqrt(x^(3n+5n)y^(n+5+3n+1))=sqrt(x^(8n)y^(4n+6))=` 

`=sqrt(x^(8n))*sqrt(y^(4n+6))=` `sqrt((x^(4n))^2)*sqrt((y^(2n+3))^2)=x^(4n)*y^(2n+3)`   

`c) \ \ sqrt(x^(5n)y^n)/sqrt(x^ny^(3n))=` `sqrt((x^(5n)y^n)/(x^ny^(3n))) \ =` `sqrt(x^(5n-n)y^(n-3n))=sqrt(x^(4n)y^(-2n))=sqrt(x^(4n))*sqrt(y^(-2n))=` `sqrt((x^(2n))^2)*sqrt((y^(-n))^2)=`  

`=x^(2n)*y^(-n)=x^(2n)*1/y^n=(x^(2n))/y^n`       ` `